DIGITAL TRANSFORMATION AND DIGITAL MATURITY IN PERTAMINA HULU ROKAN - Jusfiannur
The oil and gas industry has experienced significant volatility in the last decade because of supply and demands rapidly changing due to geopolitical, development of new technology in exploration and production, and economic situation. The COVID-19 pandemic has caused a further downturn in the oil and gas industry that is already struggling to find its profit and sustainability. The collapse of oil demand and renewed price crashes added to many challenges confronting the industry. Most executives in Oil and Gas companies are aware of the gains to be had from digitalization. Industry leaders anticipate digital applications will deliver on average a 10 percent increase in revenue due to increased production and reduced time to project start-up, and an 8.5 percent decrease in cost from improved operational efficiency, over the next 5 years. But despite its recognized potential, the digital revolution in oil and gas has not yet fully materialized. More than 70 percent of Oil and Gas companies considered themselves as being in the early stages of digital maturity. PT.Chevron Pacific Indonesia (CPI), which is one of Chevron’s upstream business units in Asia, is one of the oil companies with the longest and largest operation in Indonesia with net daily production averaged 99,000 barrels of crude oil and 19 million cubic feet of natural gas in 2019. CPI will be divested and operated by Pertamina Hulu Rokan (PHR) in Aug 2021. Impacted by the oil downturn, the company also struggles to add value to their business operations by reducing costs, increasing production, increasing the productivity of their workforce, and improving the decision-making process. They could not keep up with the pace of the corporate digital transformation journey. Digital innovation and acceleration are required for the company to resolve the issue and they need to evaluate their readiness in digital transformation and know their digital maturity. Based on the business issue above, the author conducted the research using two digital assessment frameworks to assess and analyze the Information Technology leader’s strategic thinking and organization agility, and company digital maturity. The first assessment uses a common thinking framework that digital transformation is fundamentally not about technology but human and strategy, although it may require a digital platform, the more important upgrade is its strategic thinking. The second assessment uses the TMForum Digital Maturity Model, one of many digital maturity models available in the industry, to assess the digital maturity of the company. The result from this research is expected, first, to help the company to review the digital fluency of leaders and plan for improvement in digital transformation, and second, by knowing its digital maturity, the company can analyze and properly structure and understand the nature of the problem to be addressed, facilitate the creation of goals and plans, both short- and longer-term, provide a basis to help organizations assess realistically where they are in their transformation journey, and make investments into transformational projects more effective.